Challenges to the implementation of assessment in the Merdeka Curriculum - Ahmad Muktamar (Cigarskruie: Journal of Educational and Islamic Research, 2023)
Assessment plays a central role in supporting the implementation of Merdeka Curriculum by bringing significant changes in the educational paradigm. The role of assessment in achieving learner competencies is no longer limited to measuring academic results, but also becomes a dynamic instrument for understanding students' skills, character, and creativity. Efforts to overcome challenges involve strategies such as increasing resources, comprehensive involvement of stakeholders, and education related to the Merdeka Curriculum. Innovation in assessment is a crucial solution in overcoming these challenges. The use of technology in developing assessment tools provides a new dimension in designing responsive, varied, and adaptive instruments. Best practices in designing assessments based on the Merdeka Curriculum include formative assessment, project-based approaches, and holistic assessment of student skills and character. Diversification of assessment types, including student involvement in peer assessment, provides an opportunity to create an inclusive and student-centered learning environment. Thus, the main conclusion of this discussion is that effective and innovative assessments can be a key driver of the successful implementation of Merdeka Curriculum. In navigating changes and challenges, assessment becomes a tool that guides and shapes education towards more adaptive and relevant goals. Through constant attention to innovation in assessment, the Merdeka Curriculum has the potential to create a generation that is not only academically intelligent, but also creative, independent and ready to face the demands of the future.